A comparison of the causes of blindness certifications in England and Wales in working age adults (16–64 years), 1999–2000 with 2009–2010. Issue 2 (12th February 2014) - Liew, Gerald; Michaelides, Michel; Bunce, Catey
Abstract : Objectives: To report on the causes of blindness certifications in England and Wales in working age adults (16–64 years) in 2009–2010; and to compare these with figures from 1999 to 2000. Design: Analysis of the national database of blindness certificates of vision impairment (CVIs) received by the Certifications Office. Setting and participants: Working age (16–64 years) population of England and Wales. Main outcome measures: Number and cause of blindness certifications. Results: The Certifications Office received 1756 CVIs for blindness from persons aged between 16 and 64 inclusive between 1 April 2009 and 31 March 2010. The main causes of blindness certifications were hereditary retinal disorders (354 certifications comprising 20.2% of the total), diabetic retinopathy/maculopathy (253 persons, 14.4%) and optic atrophy (248 persons, 14.1%). Together, these three leading causes accounted for almost 50% of all blindness certifications. Between 1 April 1999 and 31 March 2000, the leading causes of blindness certification were diabetic retinopathy/maculopathy (17.7%), hereditary retinal disorders (15.8%) and optic atrophy (10.1%). Conclusions: For the first time in at least five decades, diabetic retinopathy/maculopathy is no longer the leading cause of certifiable blindness among working age adults in England and Wales, having been overtaken by inherited retinal disorders. This change may be related to factors including the introduction of nationwide diabetic retinopathy screening programmes in England and Wales and improved glycaemic control. Inherited retinal disease, now representing the commonest cause of certification in the working age population, has clinical and research implications, including with respect to the provision of care/resources in the NHS and the allocation of research funding.